Ozone source apportionment over the Yangtze River Delta region, China: Investigation of regional transport, sectoral contributions and seasonal differences. (1st April 2019) - Li, Li; An, Jingyu; Huang, Ling; Yan, Rusha; Huang, Cheng; Yarwood, Greg
Abstract: With the stringent emission control measures implemented in recent years, the overall air quality in China has been improved greatly. However, high ozone (O3 ) concentrations have become a more and more severe air pollution issue in the rapidly developing Yangtze River Delta (YRD) region of eastern China including Shanghai, Jiangsu, Zhejiang and Anhui provinces. The 90 th percentile of O3 -8 h concentration in the YRD region increased from 144 μg/m 3 in 2013 to 168 μg/m 3 in 2017. To investigate the sources of O3 within the YRD region, we use a tagged-species method in the Comprehensive Air Quality Model with Extensions (CAMx) called Ozone Source Apportionment Technology (OSAT) to quantify O3 contributions by source regions and sectors in Spring, Summer and Fall. We find that the O3 pollution in Shanghai, southern Jiangsu and northern Zhejiang is caused by the joint effect of local to regional precursor emissions combined with super-regional O3 transport. However, these contributions vary among seasons and pollution events. Super regional transport is the major contributor to average O3 concentration while local and upwind adjacent area contributions can dominate during high O3 concentration episodes. Source sector analysis indicates that industry and vehicle emissions are major anthropogenic sources. Within the industrial sector, power plants, boilers, and petroleum industry are the top three contributors. Reducing super-regional O3 transport is of the most importance to lowering the O3 background but local to regional precursor emission reductions are also of great significance to control O3 episodes with collaboration at the regional level offering potential for synergistic benefits to adjacent cities. Highlights: OSAT was applied to resolve the O3 regional transport. Detailed sectoral contributions to O3 are calculated. O3 sources are compared among seasons.